2020
DOI: 10.1007/s40618-020-01422-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on psychophysical stress in patients with adrenal insufficiency: the CORTI-COVID study

Abstract: Purpose COVID-19 is a novel threat to patients with adrenal insufficiency (AI), whose life expectancy and quality (QoL) are impaired by an increased risk of infections and stress-triggered adrenal crises (AC). If infected, AI patients require prompt replacement tailoring. We assessed, in a cohort of AI patients: prevalence and clinical presentation of COVID-19; prevalence of AC and association with intercurrent COVID-19 or pandemic-related psychophysical stress; lockdown-induced emotional burden, and health-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Thus, steroid replacement may result in either hypo-or hypercortisolism and both these conditions could predispose to SARS-CoV-2 infection [10,11]. In a recently published retrospective study on 121 patients with Addison's disease under steroid supplementation, only 1 of them (0.8%) developed COVD19 [12]. It seems therefore that hypoadrenalism associated with ACC under treatment with mitotane could be associated with a higher frequency of COVID 19 than hypoadrenalism resulting from non-neoplastic diseases.…”
mentioning
confidence: 99%
“…Thus, steroid replacement may result in either hypo-or hypercortisolism and both these conditions could predispose to SARS-CoV-2 infection [10,11]. In a recently published retrospective study on 121 patients with Addison's disease under steroid supplementation, only 1 of them (0.8%) developed COVD19 [12]. It seems therefore that hypoadrenalism associated with ACC under treatment with mitotane could be associated with a higher frequency of COVID 19 than hypoadrenalism resulting from non-neoplastic diseases.…”
mentioning
confidence: 99%
“…This study also found that patients with adrenal insufficiency (AI) and having COVID-19 infections did not display severe disease complications that required hospital admission or that an increased rate of AC was reported 32 . However, AC does occur in AI patients with COVID-19 infections 33 , and the pandemic-related stress might account for some glucocorticoid up-titrations 34 . At the start of the pandemic, the need for education (sick day rules, stringent social distancing rules), equipment (sufficient glucocorticoid supplies, steroid emergency self-injection kit) and empowerment (steroid emergency card, COVID-19 guidelines) to prevent adrenal crises was highlighted by the European Endocrine Society 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no adrenal crises were reported, but pandemic-related stress accounted for 6/14 glucocorticoid up-titrations. No differences were observed amongst primary and secondary adrenal insufficiency; whereas survey results showed concerns regarding patients’ personal health and economic status, confirming that even under unconventional stress, adequately trained patients preserve a good quality of life [ 91 ].…”
Section: Sars-cov-2 Infection In Patients With Hypopituitarismmentioning
confidence: 99%